Rhizobium sp. Degradation of Legume Root Hair Cell Wall at the Site of Infection Thread Origin - Ridge, Robert W. (1985)
Using a new microinoculation technique, we demonstrated that penetration of Rhizobium sp. into the host root hair cell occurs at 20 to 22 h after inoculation. It did this by dissolving the cell wall maxtrix, leaving a layer of depolymerized wall microfibrils. Colony growth pressure “stretched” the weakened wall, forming a bulge into an interfacial zone between the wall and plasmalemma. At the same time vesicular bodies, similar to plasmalemmasomes, accumulated at the penetration site in a manner which parallels host-pathogen systems.